Graphical User Interface (GUI) In MatLab for Solving the Pulsatile Flow in Blood Vessel - Giuma, Badreddin; Vijayajothi , Paramasivam; Kahar , Osman; Mohamed Rafiq , Abdul Kadir; Kanesan , Muthusamy (2009)
Blood flow analysis is a study of measuring the blood pressure and finding its equivalent flow rate, velocity profile and wall shear stress. In this article, the relationship between blood pressure gradient, velocity profile, centreline velocity, volumetric flow rate and wall shear stress is determined analytically through a Graphical User Interface (GUI) developed using MatLab. If one of these time-dependent blood flow properties is known, i.e. pressure gradient, velocity profile, volumetric flow rate or wall shear stress, then the remaining properties can be calculated. A code is developed to solve these blood flow properties. Any time-dependent blood properties can be used as input data. These data are then digitized and saved in this code. Subsequently, these data are curve-fitted using the Fourier series. The corresponding coefficients of Fourier series are then used to calculate the blood property. Once this is obtained, the remaining three other flow properties can be subsequently calculated. This GUI serves as a learning tool for students who wish to pursue his/her knowledge in understanding the relationship of various blood flow properties of pulsatile blood flow as well as the mathematics governing pulsatile flows. (Authors' abstract)